Method for producing an ipn interpenetrating polymer network structure liquid absorbing and swelling film
Patent Information
- Application Number
- CN202510504562.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-13
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]中国发明专利申请公布文献CN115093803A提出一种锂离子电池用厚度溶胀胶带及其制备方法,采用PET基材层,可溶胀基底层,压敏胶层,可溶胀基底层是在PET基材层的表面热熔涂布形成,该发明利用PET基底层的高强度和电晕后PET基材层与可溶胀基底层之间的结合力限制,防止可溶胀基底层在MD/TD方向的溶胀,重点达成厚度方向溶胀的技术目的;该发明的可溶胀基底层采用聚三亚甲基碳酸酯,聚丁二酸丁二醇酯,以及异氰酸酯或对甲苯磺酸固化剂一起搅拌均匀后进行热熔涂布;该方法容易存在未反应完全的小分子单体残留,容易影响电池的倍率性能和循环寿命
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion batteries and / or sodium-ion batteries, and in particular relates to a membrane material applied to the outer or inner ring of a battery electrode assembly that has the function of absorbing organic electrolyte, swelling but not dissolving, and possessing compressive elasticity. Background Technology
[0002] Lithium-ion and / or sodium-ion batteries, with their high energy density and lack of memory effect, are widely used in consumer electronics, electric vehicles, energy storage, and various small power applications. To ensure consistency in battery pack assembly and improve cycle life and safety, it is desirable for the electrode assembly (positive electrode / separator / negative electrode) to maintain tight contact during charging and discharging, ensuring a relatively stable lithium-ion transport pathway. For large square and cylindrical batteries, a small gap is typically designed between the electrode assembly and the inner wall of the casing for ease of assembly. For cylindrical batteries, this gap ranges from 30-80 micrometers per side, while for large square aluminum-cased batteries or blade batteries, it ranges from 50-150 micrometers per side. In battery design, it is desirable for the termination tape surrounding the electrode assembly to swell in volume after absorbing electrolyte, thus compensating for any gaps. Specifically, it is desirable for the thickness-direction swelling deformation of the termination tape after electrolyte absorption to effectively compensate for these gaps, maintaining stable contact between the electrode assembly and the inner wall of the battery casing, as well as between the positive / negative electrode sheets and the separator within the electrode assembly. To improve battery consistency and cycle life, it is desirable for the termination tape to swell in the thickness direction without dissolving after absorbing electrolyte. The swollen termination tape should also possess compressive elasticity, which is beneficial for adapting to dimensional changes in the thickness direction during electrode charging and discharging. Termination tapes or films possessing both thickness-direction swelling after electrolyte absorption and compressive elasticity offer positive benefits for improving battery safety, consistency, and cycle life.
[0003] Chinese invention patent application CN115093803A discloses a thick swelling tape for lithium-ion batteries and its preparation method. The tape uses a PET substrate layer, a swelling base layer, and a pressure-sensitive adhesive layer. The swelling base layer is formed by hot-melt coating on the surface of the PET substrate layer. This invention utilizes the high strength of the PET substrate layer and the bonding force between the PET substrate layer and the swelling base layer after corona treatment to prevent swelling of the swelling base layer in the MD / TD direction, focusing on achieving the technical objective of swelling in the thickness direction. The swelling base layer of this invention uses polytrimethylene carbonate, polybutylene succinate, and isocyanate or p-toluenesulfonic acid curing agent, which are stirred evenly before hot-melt coating. This method is prone to leaving unreacted small molecule monomer residues, which can easily affect the rate performance and cycle life of the battery.
[0004] Another type of tape on the market uses biaxially oriented polystyrene (OPS) film as the expansion functional layer. Pressure-sensitive adhesive is coated on the surface of the OPS film. This dense OPS film is prone to dissolving after contact with ester solvents in the electrolyte, such as typical dimethyl carbonate (DMC) or diethyl carbonate (DEC). Although it has a certain viscosity after dissolution and can compensate for the gap between the electrode assembly and the inner wall of the battery casing to a certain extent, and can prevent the electrode assembly from moving along the axial direction, this type of expansion tape is unevenly distributed after absorbing liquid and dissolving, has poor compressive elasticity, and seriously insufficient elastic recovery performance. Therefore, it does not contribute much to the cycle life and consistency of the battery.
[0005] To overcome the shortcomings and deficiencies of existing technologies and products, this invention is proposed. Summary of the Invention
[0006] This invention proposes a method for manufacturing an IPN interpenetrating polymer network structure liquid-absorbing and swelling membrane material. The method is characterized by using vinyl acetate-ethylene copolymer (VAE) as the main raw material and ethylene-vinyl acetate copolymer (EVA) as the main raw material to constitute the IPN interpenetrating polymer network structure, and employing trace amounts of peroxide as a crosslinking agent. The raw materials have the following technical characteristics: the VA content in the VAE copolymer is between 60-90 wt.%; the weight percentage of the VAE copolymer in the raw material is between 60-75 wt.%; the VA content in the EVA copolymer is between 28-48 wt.%; the weight percentage of the EVA copolymer in the raw material is between 24.8-39.8 wt.%; and the weight percentage of the peroxide crosslinking agent in the raw material is between 0.10-0.40 wt.%.
[0007] The method for manufacturing an IPN interpenetrating polymer network structure liquid-absorbing and swelling film includes the following steps:
[0008] S1. High-temperature mixing and casting film formation
[0009] The above raw materials are first mixed at high temperature of 100-130℃. By controlling the thermal decomposition kinetics of the peroxide crosslinking agent in the melt, the melt is extruded through a flat die while it is still in a thermoplastic physical state. It is then rapidly solidified on the surface of the cooling roller and cast into a film. The thickness of the cast film is between 20-90 micrometers. When the cast film is wound up, it is combined and wound up together with an inert fluoroplastic separator film or PET film.
[0010] S2. After composite winding, the product is placed inside a high-pressure tank for high-temperature and high-pressure cross-linking treatment and low-temperature co-crystallization treatment.
[0011] The composite wound material is placed inside a high-pressure vessel, and the internal pressure is adjusted to between 1-5 MPa. The material is then heated to between 130-160°C, and the cast film within the composite wound material undergoes a high-temperature, high-pressure microchemical cross-linking treatment for 1-6 hours. An inert fluoroplastic separator or PET film prevents the cast film from sticking together. The material is then held under pressure and cooled to below 50°C for a low-temperature co-crystallization treatment for 2-12 hours. During the low-temperature co-crystallization treatment, the pressure inside the high-pressure vessel can be kept constant between 0.5-5 MPa. The pressure is applied by force or pulsed alternating pressure, then reduced to atmospheric pressure before discharge; after unwinding, an IPN interpenetrating polymer network structure liquid-absorbing and swelling film is obtained; in the above-mentioned cast film, the vinyl acetate-ethylene copolymer (VAE) and ethylene-vinyl acetate copolymer (EVA) undergo free radical addition reaction during micro-chemical crosslinking treatment under high temperature and high pressure, and the polymer chain segments of vinyl acetate-ethylene copolymer (VAE) and ethylene-vinyl acetate copolymer (EVA) can undergo slight chemical crosslinking to form a three-dimensional network elastomer skeleton; the remaining majority of vinyl acetate does not undergo chemical crosslinking reaction. The polymeric segments of ethylene copolymer (VAE) and ethylene-vinyl acetate copolymer (EVA) are physically entangled and dispersed within a three-dimensional network-like elastomer framework. Most of these copolymer VAE and EVA polymeric segments have not undergone chemical cross-linking. However, some adjacent polyethylene polymeric segments, after undergoing low-temperature treatment below 50°C for 2-12 hours and internal high-pressure treatment, can form co-crystallization, resulting in numerous polyethylene crystalline hard-phase micro-regions with certain mechanical strength. Using the above-mentioned raw materials and manufacturing method of this invention, chemically cross-linked and... The physically cross-linked IPN interpenetrating polymer network structure thin film material of this invention can be applied to lithium-ion batteries or sodium-ion batteries. The IPN interpenetrating polymer network structure liquid-absorbing and swelling film material of this invention possesses liquid-absorbing and swelling properties and compressive elasticity. It is insoluble in ester solvents in organic electrolytes, does not affect the cycle life and rate performance of the battery, and is beneficial to improving battery consistency and safety. When the IPN interpenetrating polymer network structure liquid-absorbing and swelling film material of this invention is immersed in dimethyl carbonate (DMC) solvent at 20-25°C for 72 hours in an organic electrolyte, the swelling ratio T in the thickness direction is [not specified]. 72h / T0 is between 2.0 and 5 times, and the swelling weight ratio W 72h / W0 is between 2.4 and 6 times, where T 72h The thickness of the membrane material after 72 hours of swelling is referred to as T0, which is the initial thickness of the membrane material before immersion; where W 72hThe total weight of the membrane material after 72 hours of liquid absorption and swelling is referred to as W0, which is the initial weight of the membrane material before immersion in the solvent. After 72 hours of liquid absorption and swelling, the liquid-absorbing and swelling membrane material of the IPN interpenetrating polymer network structure of the present invention is subjected to a pressure of 0.01 MPa in the thickness direction at an ambient temperature of 5-15°C and the pressure is maintained for 24 hours. After the pressure is removed, the compression set in the thickness direction is less than 9%.
[0012] The aforementioned IPN interpenetrating polymer network structure liquid-absorbing and swelling film material, with or without pressure-sensitive adhesive coated on one side, can be applied to the outermost ring of the electrode assembly of lithium-ion or sodium-ion batteries, or to the inner ring of the battery electrode assembly. It swells in the thickness direction after absorbing electrolyte, filling the gap between the electrode assembly and the battery casing, or improving the tight contact between the positive / negative electrode and the separator, which is beneficial to improving battery consistency, cycle life and safety.
[0013] In the casting process, before the cast film is peeled off from the surface of the cooling roller or before winding, the liquid-absorbing and swelling film material of the above-mentioned IPN interpenetrating polymer network structure is combined with a biaxially oriented high-strength PET film with a thickness of 3-6 micrometers. The PET film and the liquid-absorbing and swelling film material of the IPN interpenetrating polymer network structure form a double-layer composite film with suitable tensile strength and process adaptability, which facilitates the smooth progress of subsequent pressure-sensitive adhesive coating and slitting processes.
[0014] The IPN interpenetrating polymer network structure liquid-absorbing and swelling film obtained by the manufacturing method of the present invention can attract small molecule solvents such as dimethyl carbonate (DMC) in the organic electrolyte of lithium-ion or sodium-ion batteries into the micro-crosslinked IPN interpenetrating polymer network under capillary action after contact, achieving swelling in the thickness direction. Due to the physical restriction of the IPN interpenetrating polymer network structure, most of the polymer chain segments of the copolymer VAE or EVA that have not undergone chemical crosslinking reaction and are dispersed in the three-dimensional network elastomer skeleton will not dissolve in small molecule solvents such as DMC due to physical entanglement and the restraint and restriction of the above-mentioned polyethylene co-crystallization hard region, thereby achieving the technical purpose of liquid absorption and swelling without dissolution and possessing compressive elasticity.
[0015] The reason why the raw materials of this invention have the above-mentioned technical features and proportions, and why the above-mentioned manufacturing method are adopted, is based on the fact that this invention focuses on achieving swelling characteristics and compressive elasticity in the thickness direction of the product. If the VA content in the copolymer VAE is too low, the weight percentage of copolymer VAE in the raw materials is also too low, the VA content in copolymer EVA is also too low, and the weight percentage of copolymer EVA in the raw materials is too high, the resulting film material has high hardness and strength, but low liquid absorption and swelling characteristics. If the VA content in the copolymer VAE is too high, the weight percentage of copolymer VAE in the raw materials is also too high, the VA content in copolymer EVA is also too high, and the weight percentage of copolymer EVA in the raw materials is too low, the resulting film material has low hardness and strength, poor compressive elasticity, and the film material has an excessively large swelling ratio in the planar direction after liquid absorption, while the swelling in the thickness direction is insufficient, which can easily lead to the unfavorable result of electrode wrinkles, posing a risk of lithium plating during charging, and is detrimental to battery safety.
[0016] To better understand this invention, the following are some embodiments and comparative examples. Example
[0017] Example 1:
[0018] IPN interpenetrating polymer network structure liquid-absorbing and swelling membrane material uses vinyl acetate-ethylene VAE copolymer (mainly vinyl acetate) and ethylene-vinyl acetate copolymer (mainly ethylene) EVA as the main raw materials to form the IPN interpenetrating network structure, and uses a trace amount of peroxide as a crosslinking agent; the VA content in the VAE copolymer is between 75-85 wt.%, and the VAE copolymer accounts for 66.8 wt.% of the raw materials by weight; the VA content in the EVA copolymer is between 32-35 wt.%, and the EVA copolymer accounts for 33 wt.% of the raw materials by weight; the peroxide crosslinking agent accounts for a significant portion of the raw materials. The weight percentage is 0.20 wt.%, and the peroxide used is bis-tert-butyl peroxide (BIPB); the ethylene-vinyl acetate copolymer (EVA) raw material is EVA-3345 produced by Arkema; the vinyl acetate-based vinyl acetate-ethylene VAE copolymer uses VAE produced by emulsion polymerization, grade HS-330, with a glass transition temperature (Tg) of approximately -10℃. This raw material is from Shenzhen Gangyu Carbon Crystal Technology Co., Ltd., and is used after spray drying; the bis-tert-butyl peroxide (BIPB) is FARIDA BIPB-96 produced by Hunan Fangruida Co., Ltd. The manufacturing method of the IPN interpenetrating polymer network structure liquid-absorbing swelling film material includes the following steps:
[0019] S1. High-temperature mixing and casting film formation
[0020] The above raw materials are first mixed at high temperature at 110-120℃. By controlling the thermal decomposition kinetics of the peroxide crosslinking agent in the melt, the melt is extruded through a flat die while it is still in a thermoplastic physical state. It is then rapidly solidified on the surface of the cooling roller and cast into a film. The thickness of the cast film is between 45-50 micrometers. When the cast film is wound up, it is combined and wound up together with the inert fluoroplastic separator FEP film.
[0021] S2. After composite winding, the product is placed inside a high-pressure tank for high-temperature and high-pressure cross-linking treatment and low-temperature co-crystallization treatment.
[0022] The composite wound material is placed horizontally on a mandrel inside a high-pressure vessel and heated to a temperature range of 145-150℃. The pressure inside the high-pressure vessel is adjusted to 2-2.5MPa, and the cast film undergoes high-temperature and high-pressure microchemical crosslinking treatment for 3 hours. The inert fluoroplastic separator FEP film plays a process role in preventing the cast film from sticking together. Then, it is held under pressure and cooled to 35-40℃, and maintained in this temperature range for 8 hours for deep co-crystallization treatment. After depressurization to atmospheric pressure, the material is discharged. After unwinding, an IPN interpenetrating polymer network structure liquid-absorbing and swelling film material is obtained. The film material is immersed in dimethyl carbonate (DMC) solvent or organic electrolyte at 23-25℃ for 72 hours. The swelling ratio in the length direction is about 1.08-1.10 times, the swelling ratio in the width direction is about 1.04-1.06 times, and the swelling ratio in the thickness direction is T. 72h / T0 is between 2.7 and 2.8 times, and the swelling weight ratio W 72h / W0 is between 3.8 and 3.9 times.
[0023] After the above-mentioned IPN interpenetrating polymer network structure absorbent swelling film has absorbed liquid and swelled for 72 hours, a pressure of 0.01 MPa is applied in the thickness direction at an ambient temperature of 10-15℃ and the pressure is maintained for 24 hours. After the pressure is removed, the compression set in the thickness direction is less than 5%.
[0024] Comparative Example 1:
[0025] The liquid-absorbing and swelling membrane material uses vinyl acetate-ethylene VAE copolymer as the main raw material and a trace amount of peroxide as a crosslinking agent; the content of VA in the VAE copolymer is between 75-85 wt.%; the VAE copolymer accounts for 99.8 wt.% of the raw material by weight; the peroxide crosslinking agent accounts for 0.20 wt.% of the raw material by weight, and the peroxide used is bis-tert-butyl peroxide dicumyl peroxide (BIPB);
[0026] The liquid-absorbing and swelling film material was manufactured using the same method as in Example 1 above. After unwinding, the liquid-absorbing and swelling film material was tested by immersing it in dimethyl carbonate (DMC) solvent at 23-25°C for 72 hours. The swelling ratio in the length direction was approximately 1.8-1.9 times, the swelling ratio in the width direction was approximately 1.6-1.7 times, and the swelling ratio T in the thickness direction was... 72h / T0 is between 1.3 and 1.35 times, and the swelling weight ratio W 72h / W0 is approximately 4.9 times.
[0027] After the above-mentioned liquid-absorbing and swelling membrane material has been swollen for 72 hours, a pressure of 0.01 MPa is applied in the thickness direction at an ambient temperature of 10-15℃ and the pressure is maintained for 24 hours. After the pressure is removed, the compression set in the thickness direction is greater than 15%.
[0028] Comparative Example 2:
[0029] The liquid-absorbing and swelling membrane material uses ethylene-vinyl acetate (EVA) copolymer as the main raw material and a trace amount of peroxide as a crosslinking agent; the VA content in the EVA copolymer is between 32-35 wt.%; the EVA copolymer accounts for 99.8 wt.% of the raw materials by weight; the peroxide crosslinking agent accounts for 0.20 wt.% of the raw materials by weight, and the peroxide used is bis-tert-butyl peroxide (BIPB);
[0030] The liquid-absorbing and swelling film material was manufactured using the same method as in Example 1 above. After unwinding, the liquid-absorbing and swelling film material was tested by immersing it in dimethyl carbonate (DMC) solvent at 23-25°C for 72 hours. The swelling ratio in the length direction was approximately 1.07 times, the swelling ratio in the width direction was approximately 1.07 times, and the swelling ratio T in the thickness direction was... 72h / T0 is approximately 1.2-1.3 times, and the swelling weight ratio W 72h / W0 is approximately 1.8-1.9 times.
Claims
1. A method for manufacturing an IPN interpenetrating polymer network structure liquid-absorbing and swelling film, characterized in that, The IPN interpenetrating polymer network structure liquid-absorbing and swelling membrane material uses vinyl acetate-ethylene copolymer (VAE) and ethylene-vinyl acetate copolymer (EVA) as the main raw materials constituting the IPN interpenetrating polymer network structure, and uses a trace amount of peroxide as a crosslinking agent. The above raw materials have the following technical characteristics: the VA content in the copolymer VAE is between 60-90 wt.%; the weight percentage of copolymer VAE in the raw materials is between 60-75 wt.%; the VA content in the copolymer EVA is between 28-48 wt.%; the weight percentage of copolymer EVA in the raw materials is between 24.8-39.8 wt.%; and the weight percentage of peroxide crosslinking agent in the raw materials is between 0.10-0.40 wt.%. The IPN interpenetrating polymer network structure liquid-absorbing and swelling membrane material of this invention is immersed in dimethyl carbonate (DMC) solvent or organic electrolyte at 20-25°C for 72 hours, and the swelling ratio T in the thickness direction is... 72h / T0 is between 2.0 and 5 times, and the swelling weight ratio W 72h / W0 is between 2.4 and 6 times; after the IPN interpenetrating polymer network structure liquid-absorbing and swelling film of the present invention has been swollen for 72 hours, and then subjected to a pressure of 0.01 MPa in the thickness direction at an ambient temperature of 5-15°C for 24 hours, the compression set in the thickness direction is less than 9% after the pressure is removed; the manufacturing method of the IPN interpenetrating polymer network structure liquid-absorbing and swelling film includes the following steps: S1. High-temperature mixing and casting film formation The above raw materials are first mixed at high temperature of 100-130℃. By controlling the thermal decomposition kinetics of the peroxide crosslinking agent in the melt, the melt is extruded through a flat die while it is still in a thermoplastic physical state. It is then rapidly solidified on the surface of the cooling roller and cast into a film. The thickness of the cast film is between 20-90 micrometers. When the cast film is wound up, it is combined and wound up together with an inert fluoroplastic separator film or PET film. S2. The interior of the high-pressure tank undergoes high-temperature and high-pressure cross-linking treatment and low-temperature co-crystallization treatment. The composite wound material is placed inside a high-pressure tank, and the internal pressure is adjusted to between 1-5 MPa. It is then heated to between 130-160°C, and the cast film within the composite wound material undergoes high-temperature, high-pressure microchemical crosslinking treatment for 1-6 hours. An inert fluoroplastic separator or PET film prevents the cast film from sticking together. Then, it is held under pressure and cooled to below 50°C for low-temperature co-crystallization treatment for 2-12 hours. During the low-temperature co-crystallization treatment, the pressure inside the high-pressure tank can be a constant pressure between 0.5-5 MPa or a pulsed alternating pressure. After depressurization to atmospheric pressure, the material is discharged. Unwinding yields an IPN interpenetrating polymer network structure liquid-absorbing and swelling film. During the high-temperature, high-pressure microchemical crosslinking treatment, the vinyl acetate-ethylene copolymer (VAE) and ethylene-vinyl acetate copolymer (EVA) in the cast film undergo free radical addition reactions, allowing the polymer segments of VAE and EVA to undergo further reactions. Slight chemical cross-linking occurs, forming a three-dimensional network-like elastomer framework. The remaining polymer segments of vinyl acetate-ethylene copolymer (VAE) and ethylene-vinyl acetate copolymer (EVA), which have not undergone chemical cross-linking, are physically entangled and dispersed within the three-dimensional network-like elastomer framework. Among these copolymer VAE and EVA polymer segments, the adjacent polyethylene polymer segments, after undergoing low-temperature treatment below 50°C for 2-12 hours and internal high-pressure treatment, can form co-crystallization, resulting in many polyethylene crystalline hard-phase micro-regions with certain mechanical strength. Using the above-mentioned raw materials and manufacturing method of this invention, an IPN interpenetrating polymer network structure thin film material with both chemical and physical cross-linking can be obtained. This material can be applied to lithium-ion or sodium-ion batteries, exhibiting liquid absorption and swelling properties and compressive elasticity. It is insoluble in ester solvents in organic electrolytes, does not affect the battery's cycle life and rate performance, and is beneficial for improving battery consistency and safety.
2. The method according to claim 1, characterized in that, The above-mentioned IPN interpenetrating polymer network structure liquid-absorbing and swelling film material is coated with pressure-sensitive adhesive on one side to obtain a terminating tape with swelling function. It is applied to the outermost ring of the electrode assembly of lithium-ion battery or sodium-ion battery, and has the function of swelling after absorbing electrolyte, thus filling the gap between the electrode assembly and the battery casing.
3. The method according to claim 1, characterized in that, In the casting process, the above-mentioned IPN interpenetrating polymer network structure liquid-absorbing and swelling film is composited with a biaxially oriented high-strength PET film with a thickness of 3-6 micrometers before the cast film is peeled off from the surface of the cooling roller or before it is wound up.
Citation Information
Patent Citations
Thickness swelling adhesive tape for lithium ion battery and preparation method of thickness swelling adhesive tape
CN115093803A